STRATEGI BELAJAR ANAK BERPRESTASI DARI KELUARGA ORANG TUA YANG BERCERAI DI KOTO PANJANG KENAGARIAN TIGO JANGKO KECAMATAN LINTAU BUO KABUPATEN TANAH DATAR - Nita, Yeyes - (Pendidikan Sosiologi, 2014)
Thesis Koran on learning strategies achieving children from families of parents whodivorced in Koto Panjang subdistrict Kenegarian Tigo Jangko Lintau Buo Tanah Datar. butnot for children achieving children from divorced families were found in Koto Panjangauthor means that they can still get the achievement even though in the condition of herparents divorced this study aims to describe the learning strategies achieving children in KotoPanjang subdistrict Lintau Buo Tanah Datar. The approach used in this study is a qualitativeapproach, The results of this study showed that children performed a variety of strategies forachieving the learning process such as 1) Borrow books, among others: the senior brother,borrow books at the library, borrow books to different school friends, borrow a book forteachers, 2) Repeating the lessons at home 3) Looking for lesson materials from the internet4) Form a study group.